Digital generation online shopping users: not a secret for generation z - Yulandari, Ariefah (ProBisnis : Jurnal Manajemen, 2023)
Impulse buying is often a label for generation Z. This study was carried out to test the influence of sentiment polarity and observational learning on online impulsive buying moderated by impulsive buying tendencies. This research takes data from generation Z who live in the city of Solo who buy online. The sample obtained was 96 respondents and tested using logistic regression analysis. It was found that sentiment polarity has no effect on online impulse buying and impulse buying tendency is an ordinary independent variable that has an independent effect on impulse buying. In contrast, observational learning has a positive effect on online impulsive buying, while the impulsive buying tendency variable does not moderate the relationship between sentiment polarity and observational learning on online impulsive buying.